2020
DOI: 10.1002/mds.28144
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants Coregulate Expression of GBA and Modifier Genes to Delay Parkinson's Disease Onset

Abstract: A BS TRACT: Background: GBA mutations are numerically the most significant genetic risk factor for Parkinson's disease (PD), yet these mutations have low penetrance, suggesting additional mechanisms. Objectives: The objective of this study was to determine if the penetrance of GBA in PD can be explained by regulatory effects on GBA and modifier genes. Methods: Genetic variants associated with the regulation of GBA were identified by screening 128 common single nucleotide polymorphisms (SNPs) in the GBA locus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…The 117 trans-interchromosomal-eQTL regulated genes were significantly (p < 0.01, Kruskal-Wallis test) more intolerant to loss-of-function mutations (LOEUF 0.42 [median]; a low LOEUF score is indicative of evolutionary constraint) than those regulated by cis-or trans-intrachromosomal acting eQTLs (LOEUF 0.83 and 0.85 respectively [median]; Figure 3; Supplementary table 7). This result is consistent with earlier observations that trans-eQTLs are enriched in regulating constrained genes with low LOEUF scores 19 .…”
Section: Genes Subject To Trans-regulation By Pd-snps Are More Likely To Be Intolerant To Loss-of-function Mutationssupporting
confidence: 93%
See 2 more Smart Citations
“…The 117 trans-interchromosomal-eQTL regulated genes were significantly (p < 0.01, Kruskal-Wallis test) more intolerant to loss-of-function mutations (LOEUF 0.42 [median]; a low LOEUF score is indicative of evolutionary constraint) than those regulated by cis-or trans-intrachromosomal acting eQTLs (LOEUF 0.83 and 0.85 respectively [median]; Figure 3; Supplementary table 7). This result is consistent with earlier observations that trans-eQTLs are enriched in regulating constrained genes with low LOEUF scores 19 .…”
Section: Genes Subject To Trans-regulation By Pd-snps Are More Likely To Be Intolerant To Loss-of-function Mutationssupporting
confidence: 93%
“…Both alpha-synuclein (αSyn) protein pathology and modulation of PD-related genes have been identified in peripheral tissues (e.g. the gastrointestinal tract and heart) of PD patients 12,[14][15][16][17][18][19] . The contribution of peripheral tissue in the origins of PD warrants further research, and thus the consideration of how PD-SNPs mediate risk should not be confined to tissues of the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for common variants with low individual effect identified in previous GWAS studies, the criteria recommend calculating the PRS for a large sample series with genetic data and classifying patients according to the risk score distribution in the sample. A recent study has identified common non-coding SNPs within GBA regulating GBA expression in peripheral tissues [ 86 ]. Interestingly, the authors report that non-coding SNPs within GBA also coregulate potential modifier genes in the central nervous system and/or peripheral tissues, delaying disease onset by 5 years.…”
Section: Genetics Informs Parkinson’s Disease Subtypingmentioning
confidence: 99%
“…Notably, the phenotypic disparity among patients with GD 51 or PD 52 with the same GBA1 genotype might indicate the existence of environmental or genetic modifiers. 53,54 These modifiers could be lysosomal genes, for example, CTSB (cathepsin B) 55 or GBA2 (discussed later). Moreover, mutations in LRRK2 (leucine-rich repeat kinase 2), which participates in lysosomal function and inflammatory response, seem to alleviate GBA1 mutations effects in human induced pluripotent stem cell (iPSC)-derived neurons 56 or astrocytes.…”
Section: Parkinson's Disease and Gba1 Mutationsmentioning
confidence: 99%